1973
DOI: 10.1007/bf01856787
|View full text |Cite
|
Sign up to set email alerts
|

Der Einfluß von Atropin auf die durch intestinale Hormone induzierte Insulinsekretion des Menschen

Abstract: and Conclusions. In 35 metabolically normal subjects the effect of i.v.secretin and eholecystokinin-panereozymin (CCK/PZ) on the endocrine and exoerine pancreatic function was investigated, before and after atropine. In addition, the effect of oral, intravenous and intraduodenal administration of glucose and amino acids on blood sugar and free fatty acids before and after the injection of atropine was studied.The secretin stimulated endocrine and exoerine pancreas was not affected by atropine. However, atropin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

1976
1976
1986
1986

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…In order for a hormone to be accepted as a gastrointestinal insulinotropic hormone, several major criteria must be satisfied: (a) the hormone must be present in the gastrointestinal tract in man; (b) it must be available in purified form for study; (c) it must be insulinotropic when given in physiologic doses; (d) nutrients known to evoke enteric augmentation of insulin secretion must stimulate the release of the hormone. Certain minor criteria should also be fulfilled, namely, secretion of the hormone should be blunted by atropine since Raptus et al [7] clearly demonstrated attenuation of the enteroinsular axis by this drug, and it should be secreted in normal or excessive amounts in maturity-onset diabetics in response to oral glucose or a mixed meal. Most of the known gastrointestinal hormones fail to meet every criterion.…”
mentioning
confidence: 99%
“…In order for a hormone to be accepted as a gastrointestinal insulinotropic hormone, several major criteria must be satisfied: (a) the hormone must be present in the gastrointestinal tract in man; (b) it must be available in purified form for study; (c) it must be insulinotropic when given in physiologic doses; (d) nutrients known to evoke enteric augmentation of insulin secretion must stimulate the release of the hormone. Certain minor criteria should also be fulfilled, namely, secretion of the hormone should be blunted by atropine since Raptus et al [7] clearly demonstrated attenuation of the enteroinsular axis by this drug, and it should be secreted in normal or excessive amounts in maturity-onset diabetics in response to oral glucose or a mixed meal. Most of the known gastrointestinal hormones fail to meet every criterion.…”
mentioning
confidence: 99%
“…2). Recent studies on CCK release from the intestinal mucosa have established that it is partially mediated by cholinergic nerves as described for gastrin, while secretin release seems to be independent of the nervous system (1,3,5,10). The purpose of this study is to evaluate if the postulated increased release of CCK observed in chronic alcoholic dogs is mediated by cholinergic nerves.…”
mentioning
confidence: 99%